Burden of skin disease in two remote primary healthcare centres in northern and central Australia. Issue 3 (21st March 2019) - Thomas, Lauren; Bowen, Asha C.; Ly, Marleesa; Connors, Christine; Andrews, Ross; Tong, Steven Y. C.
Abstract: The burden of skin infections across all age groups in remote Australian Indigenous communities is currently unknown. In a retrospective audit of 439 residents from two remote communities presenting to health clinics, skin conditions were the most common reason for presentation (1603/7392, 22%) and 330/439 (75%) residents presented at least once with a skin infection. Skin infections are an under‐appreciated and dominant reason for presentation to primary healthcare centres in these indigenous communities and public health campaigns to address this should incorporate all age groups.